Calprotectin could be a potential biomarker for acute appendicitis - Ambe, Peter C. (J Transl Med, 2016)
BACKGROUND: Acute appendicitis is a common cause for a visit to the emergency department and appendectomy represents the most common emergency procedure in surgery. The rate of negative appendectomy however has remained high despite modern diagnostic apparatus. Therefore, there is need for a better preoperative screening of patients with suspected appendicitis. Calprotectin represents a predominant protein in the cytosol of neutrophil granulocytes and has been extensively investigated with regard to bowel pathologies. This study investigates the expression of calprotectin in the lumen of the vermiform appendix of patients undergoing appendectomy for suspected appendicitis. METHODS: Appendix specimens from patients undergoing emergency appendectomy for suspected acute appendicitis were examined. Acute appendicitis was confirmed on histopathology. The qualitative expression of calprotectin in the vermiform appendix specimens was analyzed using specific calprotectin antibodies. RESULTS: Vermiform appendix specimens from 52 patients (22 female and 30 male) including 11 with uncomplicated and 41 with complicated appendicitis were analyzed. Strong immunostainings were achieved with calprotectin antibody in the lumen of all specimens irrespective of the extent of appendicitis. Immunostaining was negative in the uninflamed appendix. CONCLUSIONS: High calprotectin activity could be demonstrated within the lumen of vermiform appendix specimens following appendectomy for acute appendicitis. The high luminal accumulation of calprotectin-carrying cells could be interpreted as an invitation to study the expression of calprotectin in stool as a new diagnostic aid in patients with suspected appendicitis.